Association of Serum Triglycerides in Patients with Ischaemic Stroke Admitted in Hospital with type-2 Diabetes Patients - Bhowmik, Nirmalendu Bikash; Alam, Dilruba; Islam, Md Rashedul; Habib, Rumana; Rahman, Aminur; Hassan, Zahid; Haque, Md Amirul (Bangladesh Journal of Neuroscience, 2013)
Background and Aims: Diabetes mellitus and dyslipidemia, in particular triglyceridemia pose independent risk factors of stroke. Hypertriglyceridemia implicated in the pathogenesis of ischemic stroke by imparting endothelial dysfunction, oxidative stress and lowering fibrinolytic activity. This study was aimed to explore risk incurred by blood triglyceride level for ischemic stroke in type 2 diabetic patients. Materials and Methods: A total number of 80 [50 with acute ischemic stroke and 30 without stroke] type 2 diabetic patients consecutively admitted in the neurology department, during the period of April to September 2012, fulfilling the recruitment criteria were included in the study. Ischemic stroke was confirmed by CT-scan. Informed written consent from the legal attendant of each patient was obtained. Data regarding clinicobiochemical and images studies were retrieved from patient’s record form. Results: Male to female ratio was 1.2:1 of the study subjects. Mean (±SD) age (yrs) was 61.0±10.6 in patients with ischemic stroke (Group I) and 57.0±12.3 in patients without stroke (Group II). Risk factors like BMI, lifestyle, smoking, alcohol intake did not show any statistical significance with incidence of ischemic stroke. Mean (±SD) triglyceride (mg/ dl) was 241±56 and 217±102 in Group I and Group II respectively (p=0.024). Eighty eight percent patients had triglyceride 150 mg/dl in Group I and 70 percent in Group II. Triglyceride level (mean±SD, mg/dl) was significantly higher (335±101) in overweightobese patients (BMI 25 Kg/m2) compared to those (232±68) with normal body weight (BMI<25 Kg/m2). Triglyceride level did not show statistical difference among patients having habit of smoking or not. Mean (±SD) cholesterol (mg/dl, (±SD) was 197±62 and 165±26 in Group I and Group II respectively (p=0.009). Mean (±SD) LDL-c (mg/dl) was 101±45 and 98±42 in Group I (43.8±34.4) compared to Group II (60.2±15.6) (p=0.017). Patients with atherosclerotic changes had significantly higher triglyceride (mean±SD, mg/dl) level (338±155) compared to those without (228±89) (p=0.047). Conclusions: Data concluded that hypertriglyceridemia is relatively common among the diabetic patients even in patients with apparently good glycemic control and possibly incur added risk for ischemic stroke in these patients. However, further studies are needed involving optimum number of patients to substantiate this finding and conclusively comment on the issue and to design effective prevention program to reduce the cerebrovascular morbidity and mortality. Bangladesh Journal of Neuroscience 2013; Vol. 29 (2) : 98-107